The Hamilton affair [large type] : a novel - Cobbs, Elizabeth (Wheeler Publishing, 2016)
Cobbs's (Broken Promises) second novel is a fictionalized biography that will appeal to both biography fans and general fiction readers. Cobbs's tale of Alexander Hamilton's life concentrates mostly on his wooing of future wife Elizabeth Schuyler. But it's when he is contemplating the future of a newly independent nation and questioning the morality of mankind that the story feels most alive. Beginning in 1768 and ending in 1854, the novel alternates chapters from Alexander's and Elizabeth's point of view, beginning with their respective childhoods, their first meeting, their life in the public eye, and ending from Elizabeth's perspective after Alexander's death. Nearly 100 years is a lot of ground to cover, leaving little time to dwell on the emotions of pivotal moments such as Alexander and Elizabeth's wedding or the death of George Washington. Still, the politics of the time are easy to follow, even for non-historians, and Cobbs's depiction of Hamilton will endear him in the hearts of readers and shed light on one of the most misunderstood figures in American history and the woman who shared his life. Agent: Jim Donovan, Jim Donovan Literary. (Aug.) © Copyright PWxyz, LLC. All rights reserved.